2012
DOI: 10.1111/j.2047-6310.2011.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and insulin sensitivity evaluation in obese children affected by hepatosteatosis

Abstract: Regular physical activity must be encouraged in all obese children affected by NAFLD or not, and SWA might be a possible valid tool for evaluating actual EE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…25,26 Energy Intake At 8:30 a.m., a standardized breakfast was offered (504 kcal). This is a multisensory body monitor, worn over the triceps muscle of the right arm.…”
Section: Energy Expenditurementioning
confidence: 99%
“…25,26 Energy Intake At 8:30 a.m., a standardized breakfast was offered (504 kcal). This is a multisensory body monitor, worn over the triceps muscle of the right arm.…”
Section: Energy Expenditurementioning
confidence: 99%
“…A small number of studies show no association of physical activity with ultrasound scan or biomarkers of liver fat in children, irrespective of adjustment for adiposity (10,17,18). Randomized controlled trials show beneficial effects of lifestyle interventions on markers of liver fat, including on levels of GGT and ALT providing When the median and IQR is displayed, a Mann-Whitney U test was used to check for differences between those with and without ultrasound scan liver fat.…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence for an inverse association between physical activity and NAFLD comes from cross-sectional studies using questionnaires to assess physical activity (10)(11)(12)(13)(14)(15)(16)(17)(18), thus potentially underestimating associations in comparison with objectively measured physical activity (19). Furthermore, cross-sectional studies cannot rule out reverse causation (ie, greater adiposity and associated NAFLD causing people to be less active rather).…”
Section: What Is Newmentioning
confidence: 99%
“…Fintini and colleagues (Fintini et al, 2012) observed that youth with NAFLD had significantly lower total energy expenditure, spent less time in moderate PA and more hours in sedentary activities compared with their healthy controls. Mager and colleagues (2010) in a study with Canadian youth with hepatic steatosis reported that they spent more than 65% of daily leisure time in sedentary activities such as watching television or playing computer-video games.…”
Section: Discussionmentioning
confidence: 99%